The desirable and the possible : the limits of freedom of the press in the online coverage of the ﬂight 1907 crash - Geraldes, Elen Cristina (2007)
The notion of freedom of the press is inﬂuenced by typical Modernity values and views of the world. Due to that origin one may identify as deprivers of freedom of the press the interests of news companies, censorship – explicit or concealed - and the existence of authoritarian States, which centralize or monopolize information. This article analyzes the online coverage of a massive event in the Brazilian news, the crash of ﬂ ight 1907, which occurred on September 29, 2006. Medium Theory makes crystal clear the limitations imposed on freedom of the press regarding journalism that takes place on the Web, mainly due to three traits: the need for speed – despite this velocity clouding investigation of the facts; the shortness of news items, limiting the room for interpretation; and information fragmentation, enabling the reader to only acquire an isolated perception of the happenings. There is a clear diﬀ erence between desirable information and possible news.